Deployment of maternal healthcare services at public hospitals in Pakistan: a global perspective - Rehman, Adeela; Mohamad Diah, Nurazzura (International Journal of Current Research, (IJCR), 2017)
Women’s health status in many parts of the world is influenced by the care women acquired during her motherhood time period. This paper comprised the reviews of existing literature encompasses of maternal healthcare services in public hospitals, its efficacy, quality and user’s satisfaction. Access to healthcare services is the fundamental right of every individual in any democratic state which resulted in state’s responsibility to provide ample care to all. Therefore, it is significant to examine how public hospital manages to provide quality and timely care to mother and newborns. The state’s run health systems are built with the intention to fulfill the rights and healthcare needs of each and every citizen at government expense. Among all, mother and newborn health is important consideration which needs to be given special attention. To organize efficient care structure for maternal health needs in developing countries is one of the biggest challenges due to limited resources.